Esquemas y manejo de lineas uniformes: aspectos claves en el diseno, preparacion de los viveros uniformes de evaluacion de caracteres, adaptacion y rendimiento. (Viveros tipo VPN, VIDAC, VEF) - Dessert, M. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
Problems found in the identification of uniform lines (high yield, quality, resistance to environmental factors, diseases and pests) within nursery management programs are indicated. Yields should be assessed at one or more sites, representative of the main production areas; other characteristics such as grain quality, plant architecture, earliness, and disease and pest resistance, should also be evaluated. The amount of available seed should be increased and the amount of lines decreased, selecting the best advanced lines. An alternative scheme for selection is given. Some nurseries of uniform lines are the VPN from Costa Rica, the VPN/VAN from Honduras, and the VIDAC at the regional level. (CIAT)